Preface - Jain, F.; Broadbridge, C.; Tang, H. (International Journal of High Speed Electronics and Systems, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Tang, H. (International Journal of High Speed Electronics and Systems, 2015)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Tang, H. (International Journal of High Speed Electronics and Systems, 2014)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Nanoelectronics, Nanophotonics, And Quantum Technologies: Devices And Applications - Jain, Faquir C.; Broadbridge, C.; Gherasimova, M.; Tang, Hong (World Scientific, 2025)
This timely compendium provides state-of-the-art articles covering research areas in Nanoelectronics, Nanophotonics and Quantum Technologies.Composed of contributions by renowned researchers from both the academia and industry, this useful reference text broadly illustrates relevant aspects of high-performance materials and emerging quantum and nanoscale devices for implementing high-speed electronic systems.
Google-Books-ID: h_K0EQAAQBAJ
Keywords: Computers / Quantum Computing; Technology & Engineering / Nanotechnology & MEMS; dept.phy

Optimizing K-14 instruction to infuse 21st century skills - Day, D.; Guo, C.; Ferrari, N.; Edgecumbe, H.; Broadbridge, C. (Materials Research Society Symposium Proceedings, 2013)
This multi-phased study investigates the learning outcomes of courses taught in the K-14 classroom. Specifically, the methods and practices teachers use to develop and encourage 21st Century Skills including critical thinking skills and technological fluency in all subject areas, STEM and non-STEM related, are of great interest. Currently, these skills are in high demand in fields which develop advanced materials and are the backbone of the National Academies-developed Frameworks for K-12 Science Education. Phase I participants in this study included high school and college educators while Phase II of the study will involve K-14 students. In this study, educators were asked to rate their teaching self-efficacy in two primary areas: critical thinking skills and technological fluency. This included questions related to components in their current curriculum as well as methods of assessment [e.g., rubrics]. The instrument created to measure self-efficacy was based on a modified 'Science Teaching Efficacy Belief Instrument' (STEBI). All participants were from Connecticut. Results indicate that both STEM and non-STEM related subject areas offer an equally rich array of opportunities to effectively teach critical thinking and technological fluency at a variety of educational levels. The impact of Professional Development on teacher self-efficacy was of particular importance, especially in K-12 education. © 2013 Materials Research Society.
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Mater Res Soc Symp Proc
Keywords: Advanced materials; Critical thinking; Critical thinking skills; Curricula; Educational levels; Professional development; Science education; Science teaching; Students; Teaching; Technological fluency; dept.phy

Nanoelectronics, nanophotonics, and quantum technologies - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, Haifeng (World Scientific, 2025)
Keywords: Field (mathematics); Quantum; Quantum computer; Quantum dot; Quantum entanglement; Quantum technology; dept.phy

High performance materials and devices for high-speed electronic systems - Jain, F; Broadbridge, C; Tang, H; Gherasimova, M (World Scientific Publishing Co. Pte. Ltd., 2018)
In this review volume, the editors have included the state-of-the-art research and development in nano composites, and optical electronics written by experts in the field. In addition, it also covers applications for emerging technologies in High-Speed Electronics. In summary, topics covered in this volume includes various aspects of high performance materials and devices for implementing High-Speed Electronic systems. © 2019 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.
Keywords: Emerging technologies; High performance material; High-speed electronics; Materials; Nanocomposites; Optical electronics; State of the art; dept.phy

High performance logic and circuits for high-speed electronic systems - Jain, F; Broadbridge, C; Gherasimova, M; Tang, H (World Scientific Publishing Co., 2019)
In this volume, we have put together papers spanning a broad range from the area of modeling of strain and misfit dislocation densities, microwave absorption characteristics of nanocomposites, to X-ray diffraction studies. Specific topics in this volume include: Modeling of strain relaxation and defect dynamics in buffer layers for semiconductor devices fabricated on lattice-mismatched substrates, which enables technology for advanced computer chips, multi-junction solar cells, detectors, and microwave transistors. Physical Unclonable Functions (PUFs) are probabilistic circuit primitives that extract randomness from the physical characteristics of devices. One of the papers outlines PUF design based on resistor and capacitor variations for low pass filters (LoPUF). Spatial wavefunction switching (SWS) FETs, which can process 2-bits per FET using CMOS-SWS logic, thus enabling multivalued logic (MVL) and compact DRAMs. Perimeter gated single-photon avalanche diode (PGSPAD). The applied voltage at the gate terminal modulates the electric field, making it uniform throughout the junction. This gating technique is an efficient method to prevent premature edge breakdown, one of the major problems in operating avalanche photodiodes implemented in CMOS process. In summary, papers selected in this volume cover various aspects of high performance logic and circuits for high-speed electronic systems. © 2019 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2019)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (High Performance Logic and Circuits for High-Speed Electronic Systems, 2019)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.C.; Broadbridge, C.; Tang, H.; Gherasimova, M. (High Performance Materials and Devices for High-Speed Electronic Systems, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: Materials; dept.phy

Preface - Jain, F.; Broadbridge, C.; Tang, H.; Gherasimova, M. (International Journal of High Speed Electronics and Systems, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (Nanostructures For Electronics, Photonics, Biosensors, And Emerging Systems Applications, 2022)
0 citations (Crossref) [2023-10-31] ISBN: 9789811270796
Keywords: dept.phy

Visualizing bone porosities using a tabletop scanning electron microscope - Krishnamoorthy, D.; DaPonte, J.; Broadbridge, C. C.; Daniel, D.; Alter, L. (Visual Information Processing XIX, 2010)
Pores are naturally occurring entities in bone. Changes in pore size and number are often associated with diseases such as Osteoporosis and even microgravity during spaceflight. Studying bone perforations may yield great insight into bone's material properties, including bone density and may contribute to identifying therapies to halt or potentially reverse bone loss. Current technologies used in this field include nuclear magnetic resonance, micro-computed tomography and the field emission scanning electron microscope (FE-SEM)^ 2, 5. However, limitations in each method limit further advancement. The objective of this study was to assess the effectiveness of using a new generation of analytical instruments, the TM-1000 tabletop, SEM with back-scatter electron (BSE) detector, to analyze cortical bone porosities. Hind limb unloaded and age-based controlled mouse femurs were extracted and tested in vitro for changes in pores on the periosteal surface. An important advantage of using the tabletop is the simplified sample preparation that excludes extra coatings, dehydration and fixation steps that are otherwise required for conventional SEM. For quantitative data, pores were treated as particles in order to use an analyze particles feature in the NIH ImageJ software. Several image-processing techniques for background smoothing, thresholding and filtering were employed to produce a binary image suitable for particle analysis. It was hypothesized that the unloaded bones would show an increase in pore area, as the lack of mechanical loading would affect bone-remodeling processes taking place in and around pores. Preliminary results suggest only a slight different in frequency but not in size of pores between unloaded and control femurs.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/004-681-726-544-835, pop00157 tex.type: [object Object]
Keywords: Bone; Computerized tomography; Data processing; Electron microscopes; Electrons; Intracortical; Mammals; Particle analysis; Periosteal; Resonance; Scanning; Scanning electron microscope; Scanning electron microscopy; Threshold; Tomography; dept.phy

An inquiry-based course in nano-photonics - Broadbridge, C.; Calvert, J.; Donnelly, J.; Garofano, J.; Massa, N. (Proc SPIE Int Soc Opt Eng, 2010)
We developed a curriculum to introduce nanotechnology and photonics concepts to community college students enrolled in a program designed to attract and retain students in technology associate degree programs. Working with the Center for Research on Interface Structures and Phenomena, an NSF Materials Research Science and Engineering Center, and the PHOTON projects, funded by the Advanced Technological Education program of NSF, we developed hands-on, inquiry-based activities to address the course goals: improve critical thinking, introduce science and technology concepts common to technology programs and provide opportunity to practice math skills in context. © 2010 SPIE.
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Proc SPIE Int Soc Opt Eng
Keywords: Advanced Technological Education; Associate degree; Community college; Critical thinking; Curricula; Education; Inquiry; Interface structures; Materials research; Math skills; Nano-photonics; Nanotechnology; Photonics; Science and Technology; Science and engineering; Students; Technology programs; dept.phy

Nanotechnology for Electronics, Photonics, Biosensors, and Emerging Technologies - Jain, F.; Broadbridge, C. C.; Gherasimova, M.; Tang, H.; Connecticut Microelectronics and Optoelectronics Consortium New Haven, Conn) (World Scientific, 2021)
Keywords: Congresses; Congresses; Biosensors; Congresses; Nanoelectronics; Congresses; Nanophotonics; Congresses; Optoelectronics; Nanotechnology; dept.phy; faculty_collection

MOCVD growth and characterization of AlGaInN nanowires and nanostructures - Han, J.; Kim, K.; Su, J.; Gherasimova, M.; Nurmikko, A.V.; Chichibu, S.F.; Broadbridge, C. (Mater Res Soc Symp Proc, 2006)
Growth of GaN and AlGaInN nanowires using metalorganic chemical vapor deposition (MOCVD) is investigated. It is determined that surface kinetics play an important role in non-equilibrium synthesis process such as MOCVD, in contrast to near-equilibrium synthesis by hotwall furnace reactor. Examination of crystallographic properties of GaN nanowires reveals preferential growth directions which are perpendicular to the c-axis. Such a tendency is analyzed by both thermodynamic and kinetic arguments and attributed to the minimization of (side wall) surface energy. Spontaneous formation of Al(Ga)N/GaN coaxial nanowires with distinct emission at 370 nm is observed. It is identified that the interplay between surface kinetics and thermodynamics facilitates the catalytic growth of GaN core while a limited surface diffusion of Al adatoms leads to nonselective, vapor-solid growth of Al(Ga)N sheath. The knowledge of crystallographic alignment is applied to the formation of arrayed GaN nanowires in both vertical and horizontal fashions, resulting in potentially new paradigms for creating nanoscale devices. © 2006 Materials Research Society.
Journal Abbreviation: Mater Res Soc Symp Proc
Keywords: Crystal growth; Crystallography; Diffusion; Growth directions; Interfacial energy; Metallorganic chemical vapor deposition; Nanostructured materials; Nanostructures; Nanotechnology; Nanowires; Semiconductor quantum wires; dept.phy; non equilibrium synthesis

Improving 4H-SiC/SiO2 interface properties by depositing ultra-thin Si nitride layer prior to formation of SiO2 and annealing - Wang, X.W.; Bu, H.M.; Laube, B.L.; Caragianis-Broadbridge, C.; Ma, T.P. (Mater. Sci. Forum, 2002)
We report dramatic improvement in electrical properties of 4H-SiC/SiO2 interface by depositing an ultra-thin layer of silicon nitride on 4H-SiC prior to formation of silicon oxide and annealing. AC conductance measurements reveal interface-trap density equal to or below 1 × 1012/cm2- eV at energies near the conduction band edge. XPS spectra confirm the presence of N at the interface and suggest possible bonding between N and C. © (2002) Trans Tech Publications, Switzerland.
1 citations (Crossref) [2023-10-31] Journal Abbreviation: Mater. Sci. Forum
Keywords: 4H-SiC MOS; Angle-resolved; Angle-resolved x-ray; Annealing; Chemical bonds; Conductance measurement; Conduction band edge; Deposition; Gate dielectrics; Interface trap density; Interfaces (materials); MOS devices; Nitride layers; Nitrides; Photoelectron spectroscopy; Photoelectron spectroscopy (ARXPS); Si-CMOS; SiC/siO2-interfaces; Silica; Silicon carbide; Silicon nitride; Silicon oxides; Ultrathin films; Ultrathin layers; X ray photoelectron spectroscopy; dept.phy

Characterization of nanoparticles by computer imaging particle analysis - DaPonte, J.; Sadowski, T.; Broadbridge, C. C.; Munhutu, P.; Lehman, A.; Krishnamoorthy, D.; Garcia, E. C.; Sawicki, M. S.; Heyden, C.; Mirabelle, L.; Benjamin, P. (Nanomaterials Synthesis, Interfacing, and Integrating in Devices, Circuits, and Systems II, 2007)
Nanoparticles, particles with a diameter of 1-100 nanometers (nm), are of interest in many applications including device fabrication, quantum computing, and sensing because their decreased size may give rise to certain properties that are very different from those exhibited by bulk materials. Further advancement of nanotechnology cannot be realized without an increased understanding of nanoparticle properties such as size (diameter) and size distribution. Frequently, these parameters are evaluated using numerous imaging modalities including transmission electron microscopy (TEM) and atomic force microscopy (AFM). In the past, these parameters have been obtained from digitized images by manually measuring and counting many of these nanoparticles, a task that is highly subjective and labor intensive. Recently, computer imaging particle analysis routines that count and measure objects in a binary image^1 have emerged as an objective and rapid alternative to manual techniques. In this paper a procedure is described that can be used to preprocess a set of gray scale images so that they are correctly thresholded into binary images prior to a particle analysis ultimately resulting in a more accurate assessment of the size and frequency (size distribution) of nanoparticles. Particle analysis was performed on two types of calibration samples imaged using AFM and TEM. Additionally, results of particle analysis can be used for identifying and removing small noise particles from the image. This filtering technique is based on identifying the location of small particles in the binary image, assessing their size, and removing them without affecting the size of other larger particles.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/032-875-618-829-762, pop00276
Keywords: Atomic force microscopy; Bulk materials; Computer imaging; Device fabrication; Imaging techniques; Nanoparticles; Particle analysis; Quantum computers; Size distribution; Thresholding; Transmission electron microscopy; dept.csc; dept.phy

Effect of binder concentration on ternary MnO2/CuS/reduced graphene oxide material for supercapacitor applications - Chaudhary, Manika; Oyelola, Lekan; Glidden, Thomas; Broadbridge, C.; LeMaire, Peter; Sharma, Rakesh; Singh, Vinamrita; Sahi, Vikhyat; Singhal, Rahúl (Journal of Solid State Electrochemistry, 2025)
Keywords: Capacitance; Chemical engineering; Chemistry; Electrochemistry; Electrode; Energy storage; Graphene; Inorganic chemistry; Materials science; Metallurgy; Nanotechnology; Oxide; Physical chemistry; Supercapacitor; Synthesis; Ternary operation; Thermodynamics; X-ray diffraction; dept.phy

The effectiveness of multimedia and activity-based supplemental teaching resources in materials science education - Day, D.A.; Abbasi, E.; Liang, B.; Bhat, S.; DeMeo, S.; Garofano, J.; Grober, L.; Ferrari, N.; Broadbridge, C. (Materials Research Society Symposium Proceedings, 2012)
A comparative study investigating the integration of supplemental teaching resources in materials science education was developed for the purpose of determining the effectiveness of teaching strategies. Digital stories created by students, excerpts from the Nova Making Stuff documentaries, YouTube educational videos and student generated demo-kits were used as part of the investigation whereby two 9th grade science classes (n∼26) were evaluated. Each participant in the study received one period (40-min) of a traditional lesson on Materials Science including specific content, vocabulary, and a pre- and post- lesson assessment. Additionally, the students in each class participated in a 30-min supplemental component, e.g. video or activity-based demonstration using aforementioned kits or video compilation. Pre- and post- evaluations (e.g. open-ended and likert questions) were administered to all of the participants. As hypothesized, the students' feedback and performance on assessment activities reveal that the use of multimedia and activity-based resources may be equally effective teaching methods as traditional methods. © 2012 Materials Research Society.
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Mater Res Soc Symp Proc
Keywords: Activity-based; Assessment activities; Comparative studies; Educational videos; Effective teaching methods; Materials science; Multimedia systems; Students; Teaching resources; Teaching strategy; YouTube; dept.phy